Community Service Information System in Capital Lending at the Aceh Cooperatives, Small and Medium Enterprises Service - Mahadhir (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2021)
The aim of this research is; 1) To find out the public service information system in lending capital at the Aceh Cooperatives, Small and Medium Enterprises Service, and 2) To design a public service information system in lending capital at the Aceh Cooperatives, Small and Medium Enterprises Service. The design of public service information system software in web-based capital lending at the Aceh Cooperatives, Small and Medium Enterprises Service which the author designed consists of several stages, namely input design, output design, process design, control design, labor design, and cost design. This design later the author hopes to make it easier for every user, especially the capital loan section of the Aceh Cooperatives, Small and Medium Enterprises Office for more detailed design stages. At the application development stage using the agile development method. Based on the results of observations and the author can draw a conclusion which include the following; 1) The use of the Community Service Information System in Lending Capital at the Aceh Cooperatives, Small and Medium Enterprises Service is expected to help create accurate and effective loan information data, 2) The existence of an information system provides convenience for the Aceh Cooperatives, Small and Medium Enterprises Office because it speeds up general information and reduce errors, and 3) Sales Information System at the Aceh Cooperatives, Small and Medium Enterprises Service which the author designed using various web-based programming languages ​​consisting of; HTML, CSS, Jquery, Java Script, JSON PHP, and for database processing the Structure Query Language (SQLL) is used. The supporting software used is XAMPP version 5.6 (Support MySQLi), NotePad ++, and Google Chrome Browser.